2020
DOI: 10.4081/jphr.2020.1815
|View full text |Cite
|
Sign up to set email alerts
|

Mother's Knowledge and Attitudes towards Visual Acetate Acid Inspection Test in Surabaya

Abstract: Background: The incidence of cervical cancer in Indonesia is still high due to the poor awareness of married women about the necessity to check themselves with a pap smear/IVA test for early detection and possible cure. The implementation of the IVA examination still experiences obstacles due to lack of knowledge and fear. Design and Methods: This study aims to determine the relationship between knowledge and attitudes of mothers with IVA test, using the analytical and cross-sectional study. Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(40 citation statements)
references
References 5 publications
0
30
0
10
Order By: Relevance
“…Two studies reported pap smears for CCS [ 72 , 73 ], while two studies reported both pap smear and VIA [ 81 , 82 ]. The prevalence of having a screening done in the past ranged from 5.5% to 33.3% [ 71 , 72 , 73 , 76 , 80 , 81 , 85 ], while participants’ desire to screen was 45.2% and 57.4% based on two studies [ 77 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies reported pap smears for CCS [ 72 , 73 ], while two studies reported both pap smear and VIA [ 81 , 82 ]. The prevalence of having a screening done in the past ranged from 5.5% to 33.3% [ 71 , 72 , 73 , 76 , 80 , 81 , 85 ], while participants’ desire to screen was 45.2% and 57.4% based on two studies [ 77 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…No studies reported barriers related to demographics or socio-economic status. Embarrassment [ 74 , 81 ], knowledge deficits in CCS [ 81 , 84 ], having no symptoms [ 74 , 81 ], and fear of result [ 76 , 81 ], were among the top barriers in Indonesia. Two studies described the lack of knowledge of cervical cancer as a barrier to CCS, which was only reported in Indonesia [ 74 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of support was commonly characterised as any emotional or tangible support such as active encouragement to seek CC screening, assistance to attend services or to access information or to provide an open and positive communication about the topic. Fourteen publications discussed the positive impact of such support on women’s CC screening uptake and were conducted in West, Central and East Java [ 22 , 23 , 35–38 , 40 , 45 , 49 , 53 , 55–57 , 62 ]. Husband support was stated as a significant facilitator for increasing CC screening uptake in multiple studies across West, Central and East Java (n = 6) [ 22 , 35–37 , 49 , 55 ].…”
Section: Facilitators Of CC Uptake and Deliverymentioning
confidence: 99%
“…Fourteen publications discussed the positive impact of such support on women’s CC screening uptake and were conducted in West, Central and East Java [ 22 , 23 , 35–38 , 40 , 45 , 49 , 53 , 55–57 , 62 ]. Husband support was stated as a significant facilitator for increasing CC screening uptake in multiple studies across West, Central and East Java (n = 6) [ 22 , 35–37 , 49 , 55 ]. Husband support included gaining permission from spouses to access CC screening services, being encouraged or advised by spouses to seek CC screening services and being accompanied to CC screening services by one’s husband.…”
Section: Facilitators Of CC Uptake and Deliverymentioning
confidence: 99%